2011
DOI: 10.3324/haematol.2011.053199
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thymus and activation-regulated chemokine as an early response marker in classical Hodgkin's lymphoma

Abstract: The online version of this article has a Supplementary Appendix. BackgroundPlasma thymus and activation-regulated chemokine is a potential biomarker for classical Hodgkin's lymphoma. To define its value as a marker to monitor treatment response, we correlated serial plasma thymus and activation-regulated chemokine levels with clinical response in newly diagnosed and relapsed classical Hodgkin's lymphoma patients. Design and MethodsPlasma was collected from 60 (39 early stage and 21 advanced stage) newly diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 35 publications
(36 reference statements)
11
75
2
Order By: Relevance
“…1B). Thus, the patient cohort presented here confirmed previous data from smaller cohorts [9][10][11].…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…1B). Thus, the patient cohort presented here confirmed previous data from smaller cohorts [9][10][11].…”
Section: Resultssupporting
confidence: 79%
“…Interestingly, elevated TARC levels were also reported for patients not responding to chemotherapy after treatment initiation [10]. A more recent study reported a significant decrease in TARC levels as early as after one cycle of chemotherapy in all responsive patients [11]. From a total of 60 patients, three were resistant to standard chemotherapy and only in these patients TARC levels failed to decrease [11].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition to interim PET, biomarkers such as the thymus and activation-regulated chemokine (TARC), the number of CD68-positive macrophages in the tumor tissue or others might be included in a score predicting the individual patient's risk [17][18][19][20]. Furthermore, treatment could be optimized by combining conventional chemotherapy with novel targeted and less toxic drugs.…”
Section: Treatment Of Advanced Stagesmentioning
confidence: 99%